Local Dynamics of a Laser with Rapidly Oscillating Parameters - E. V. Grigorieva; S. A. Kaschenko (Моделирование и анализ информационных систем)
The dynamics of class B lasers with the incoherent optical feedback formed by quickly vibrating external mirrors is viewed. The problem of the stability of equilibrium in a model system with rapidly oscillating coefficients is studied. The averaged system with the distributed delay is received. It is determined that in the presence of fast delay oscillation the limit of instability of a balance state moves towards significantly greater values of the feedback coefficient. The dependence of the shift with increasing the amplitude modulation has a band structure, so the rapid oscillations of delay can stabilize or destabilize the equilibrium. Normal forms which show changes of the sign of Lyapunov quantityalong border are constructed. They describe characteristics of periodic and quasiperiodic modes close to the balance state.